"I Love These Girls—I Was These Girls": Women Leading for Social Justice in a Single-Sex Public School. Issue 4 (July 2013) - Mansfield, Katherine Cumings
The purpose of this article is to share the findings from a 2-year ethnography that examined female practitioners' experiences in the field. The article describes the intentions, discourses, actions, and repercussions of female administrators and teachers working to accomplish social justice for racial/ethnic minority girls from challenging economic circumstances. The discourse adjoining social justice intentions and actions is shared with descriptions of the specific material, intellectual, and emotional ways that female educators labored for social justice in their particular context. The impact of taking an explicitly activist stance in facilitating transformative learning opportunities is discussed along with implications for practice.